دراسة مقارنة لمفهوم الذات لدى المعاقين سمعيا الممارسين وغير الممارسين للنشاط الرياضي التنافسي المكيف -دراسـة ميدانية أجريت على الأفراد الصم البكم الممارسين وغير الممارسين بولاية الجزائر- - benabderrahmane, belkacem; Zaouak , Mhamed (sports creativity, 2025)
This study aims at revealing the differences in the self-concept of hearing impaired practitioners and non-practitioners of the adaptive competitive sports activity, to include a sample of practitioners of sports activity regularly athletes at level of different sports clubs for the deaf mute in wilaya of Algeria in addition to a non-practice sample, and the researchers relied on the descriptive approach With the field study tool represented in the scale of the concept of the self after its adaptation, the study found that there are statistically significant differences in the self-concept of the self between hearing impaired practitioners and non-practitioners of the adaptive